NOTES TO THE EUROPEAN RECOMMENDATIONS OF ACUTE MYOCARDIAL INFARCTION IN PATIENTS PRESENTING WITH ST-SEGMENT ELEVATION (Столичная издательская компания, 2015)
Notes to the european recommendations of acute myocardial infarction in patients presenting with ST-segment elevation.